Cloning of the DlERF10 gene from Diospyros lotus L. and cold tolerance analysis of the DlERF10 gene in transgenic tobacco plants - Ruijin Zhou; Shuda Li; Xiaona Zhang; Yingying Wang; Huiling Hu (PLoS ONE, 2025)
In the north of China, Diospyros plants are vulnerable to low-temperature damage in winter and is considered as a major factor restricting the development of the persimmon industry in Northern China. Diospyros lotus L. is featured by high survival potential of seedlings, cold tolerance, and grafting affinity with D. kaki Thunb. D. lotus has been frequently used as rootstocks for Diospyros spp. ERF transcriptional factors are a subfamily of the AP2/ERF gene family and play an important role in plant growth and stress tolerance. To explore the structure and function of the ERF transcription factors in D. lotus, we performed RT-PCR to clone DlERF10 from the leaves. The DlERF10 gene was 1104 bp long, encoding 367 amino acids. In order to deeply study the cold tolerance of DlERF10 gene, the pBI121-DlERF10 overexpression vector was constructed, and agrobacterium-mediated transformation was carried out to transfer the gene into tobacco plants. The wild-type and transgenic tobacco plants were subjected to low-temperature stress. The results showed that the transgenic plants were less severely damaged by low-temperature stress than the wild-type plants. Besides, the SOD, POD and CAT activities of leaves enhanced, and PRO contents of leaves increased, while the MDA content decreased. It was concluded that the DlERF10 gene increased the activity of protective enzymes in tobacco plants, thereby strengthening the tolerance to low-temperature stress. The present study proposes a candidate gene for engineering cold stress tolerance in Diospyros spp.